EWALUACJA ROLI SPOŁECZNEJ NAUCZYCIELI JĘZYKA NIEMIECKIEGO W KONTEKŚCIE ZABURZENIA STABILIZACJI ZAWODOWEJ - Ewa Papierz-Łapsa, (Neofilolog, 2019)
In an era of dynamically changing socio-economics and technological progress, many aspects of school education are being transformed. Teachers are required to be professional in the form of a demand for increasingly higher professional qualifications and competences, but are also required to fulfil specific social roles. These new determinants of the functioning of education create difficulties in the construction of the teacher's identity because the changes which are being introduced disturb professional stability and cause fears about the future. The challenge is to try to answer universal questions about the professional identity of the teacher, the ability to combine an exceptional sense of service, vocation and mission. This situation affects teachers of German and other foreign languages (FL). The aim of this paper is to show how teachers of German as a FL perceive the changing school and how they assess the educational process that they co-create. Through biographical interviews, analyzed within the framework of Rubacha’s social role model (2000), an attempt is made to answer the question of how the social role of German teachers is changing as a result of the educational reform initiated in 2017 and what dilemmas are being caused by the changing role of the teacher. Statements from participants of the study will be presented that illustrate the disorder of stabilization of the profession, which results in a critical attitude to the changing situation in school, a disturbed attitude to the world, culture and other people. Impairment of the professional stabilization of German teachers is viewed in the context of the concept of their social role.